Postgraduate's Personal Knowledge Management Using Cloud Services - Atichart Harncharnchai (2018)
© 2018 IEEE. Due to an emphasis on postgraduate's expectation regarding academic quality, various learning strategies have been proposed. In this study, the process of personal knowledge management and cloud services are used to encourage personalized learning on the selected knowledge topics. Adapted from prior learning process and PKM models, the proposed PKM model is developed comprising a series of stages: Learning engagement, creating concept, building personal knowledge base and applying knowledge. Of the two groups, a total of 19 postgraduate students taking a 'Applications of ICT' course of Knowledge Management program at Chiang Mai University, Thailand were the sample of a study, each of which was conducted over a 2-month period. The results revealed that there was no significant difference in a mean score between two groups on the test of understandings on the given knowledge topics, showing the students' average test score to exceed the minimum pass mark. The students' satisfaction level on personalized learning as supported by the PKM was also high.